Measurement of very low (α, n) cross sections of astrophysical interest. Issue 1 (January 2016) - Tain, J L; Jordán, D; Agramunt, J; Algora, A; Bandac, I; Bettini, A; Caballero-Folch, R; Calviño, F; Cano-Ott, D; Cortés, G; Domingo-Pardo, C; Fraile, L M; et al.
Abstract: The reactions 13 C(α, n) 16 O and 22 Ne(α, n) 25 Mg are the primary sources of neutrons for the astrophysical s -process. The feasibility of cross section measurements within the respective Gamow windows is discussed in quantitative terms for a 4π neutron counter, based on 3 He tubes and a neutron moderator, placed in an underground lab.